(untitled) (Research, Society and Development, 2022)
Barra Grande, a village located in the municipality of Cajueiro da Praia-PI, Brazil, is considered one of the main national and international tourist destinations for Kitesurfing nowadays. With this in mind, the present study aims to map and analyze the Brazilian scientific production on kitesurfing in this location, in order to understand how Brazilian researchers approach this sport in their studies. This research has a qualitative nature that adopted as a strategy, for exploratory and descriptive purposes, the bibliographic literature review, which was carried out in the Capes Theses and Dissertations Catalog database, in productions published from 2000 to 2021. The results showed for 105 works, between theses and dissertations, eight dissertations being selected for analysis. With the treatment of the data, it was found that the works are, mostly (62.50%), produced in Graduate Programs of the Federal University of Piauí (UFPI), with emphasis on the areas of Anthropology and Archeology. Tourism and development in Barra Grande are the main topics discussed, with kitesurfing being the main driver of these phenomena in recent decades. Scientific production is still scarce and needs further studies. Although kitesurfing is investigated in a secondary way in the analyzed works, its importance for the recognition of the village as a national and international tourist destination is noted.